Supervisory Function of the Regional People's Representative Council in Managing the Regional Budget in west Sulawesi Province - Ibadurrahman; Supiati; Abdul Rahman (Universitas Muhammadiyah Palu, 2023)
The method used in this research is qualitative with the type of qualitative descriptive research method. The population is all employees of the Regional People's Representative Council (DPRD) of West Sulawesi Province as many as 45 people. The sampling technique uses (Purposive sampling) a determination technique with special considerations so that it is feasible to be a sample of 9 people and is determined by researchers. The data is analyzed descriptively qualitatively. Data collection techniques using observation, interviews, and documentation. The results in this study indicate that the oversight function carried out by the Regional People's Representative Council (DPRD) in the Management of the Regional Expenditure Budget (APBD) in West Sulawesi Province in the supervisory planning stage has a supervisory role in the preparation stage of the APBD PERDA which starts from APBD preparation activities, socialization , preparation to the DPRD, discussion, decision making, evaluation and finally the determination of the APBD which will be carried out in one fiscal year. The implementation of supervision carried out by the Regional People's Legislative Council (DPRD) on the absorption of the APBD budget that in effectiveness and efficiency in absorbing the use of the APBD budget has not reached the maximum goal and the measure of success in using the budget has not been maximized because the program for each OPD was previously determined due to trimming and budget cuts every OPD. Evaluation Supervision is carried out both on the administration of government and regarding the use of the Regional Revenue and Expenditure Budget (APBD) by the Audit Board of the Republic of Indonesia (BPK), this institution has the authority to examine the management and accountability of state finances. (DPRD). Financial and Development Supervisory Agency (BPKP).